Adsorption of organic dyes in graphene: an Ab Initio study - Cargnelutti, Jessica; Oliveira, Patricia Viera de; Jauris, Iuri Medeiros; Silva, Ivana Zanella da; Fagan, Solange Binotto (Disciplinarum Scientia | Naturais e Tecnológicas, 2019)
Inadequate disposal of organic dyes in aquatic effluents can cause unfavorable effects on flora and fauna by obstructing the transmittance of solar radiation, thus preventing photosynthesis by algae and causing serious damage to humans such as irritation, allergy, mutagenic and carcinogenic effects. On looking for new efficient alternatives and a low cost of adsorption of these organic compounds, we propose a study of graphene in interaction with the Methylene Blue (MB), Acridine Orange (AO) and Red Alizarin S (ARS) dyes via computational simulations evaluating their electronic and structural properties. In this study, the Density Functional Theory (DFT) was implemented in the SIESTA computational code to perform the electronic structure calculations of the systems. It has been observed that the most stable configurations are those in which graphene is in the planar position with the nanostructure. The MB dye is the one with the highest stability with a binding energy of 1.86 eV. Upon comparing this same configuration with the methodology of the carbon nanotubes we have the energy of 1.14 eV. Thus, we can conclude that graphene becomes more efficient than nanotubes in the adsorption of organic dyes.